STEROIDS X AROMATIZATION EXPERIMENTS IN THE CHOLESTEROL SERIES - ROSENKRANZ, G; ROMO ARMERIA, JESUS; DJERASSI, CARL (LABORATORIOS SYNTEX, CD. MEXICO, DF, MEX, 1951)
Aromatization of a tetralin solution of 1,4,6-cholestatrien-3-one (V) at 700Â° produced 3-hydroxy-19-nor-1,3,5,6-cholestatetraene (VI), which on hydrogenation led to the phenol VII, an analog of cholesterol possessing an aromatic ring A. Both phenols were
J REPROD FERTIL
Keywords: STEROIDS, AROMATIZATION EXPERIMENTS, CHOLESTEROL SERIES; QUIMICA; QUIMICA ORGANICA; QUIMICA DE LOS ASTEROIDES